Penerimaan Khalayak pada Konten Youtube Gamal: Episode Akar Permasalahan di Dunia - Muhammad Fa’isal; Rakhmad S. Ramadhani; Masnia Ningsih (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Neo-feudalism Analisis Resepsi, Fariz Egia Gamal, Akar Permasalahan Di Dunia, Neo Feodalisme describes the resurgence of social and economic patterns resembling medieval feudalism in a modern context. This phenomenon is characterized by increasing social and economic inequality and the concentration of wealth and influence among a few individuals or groups, reflects a distribution structure similar to that implemented in the feudal system of the past. This study aims to analyze the audience reception of Gamal's YouTube content in the episode